LONG STYLOID PROCESS – EAGLE SYNDROME; UNUSUAL CAUSE OF SUDDEN NATURAL DEATH – A CASE REPORT (Journal of Forensic Medicine & Toxicology, 2017)
Approximately 80 percent of sudden natural deaths are said to be cardiac in origin and the greater part is due to coronary atherosclerosis producing ischaemic heart disease. The relatively uncommon conditions associated with sudden death include electrolyte imbalance, ruptured ectopic pregnancy, and pancreatitis, hypothermia etc. The current case however enlightens one abnormal anatomical finding of long styloid process Eagle syndrome which can, though rare, be a cause of sudden and unexpected death.
Keywords: Eagle syndrome; Long Styloid Process; Sudden Death